(untitled) (World Bulletin of Public Health, 2025)
Urinary tract infections is a common problem in Kirkuk province especially among children in pediatric hospital. Objective: The objective of this study was to clarify the distribution of urinary tract infections among children in Kirkuk pediatric hospital. Methods: A cross sectional study was conducted on 135 children with UTI, attended Kirkuk pediatric hospital during period from beginning of February to end of July 2025. The age of UTI children was ranging from below one year to 14 years. General urine examination was performed for each child and urine culture done for infected child